Assessing The Association Between Plantar Fasciitis and Hyperuricemia - Alam, Syed Asadullah; Amin, Muhammad Suhail; Chodhry, Nadeem; Mushtaq, Ahmed; Haseeb, Malik; Riaz, Arsalan (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of hyperuricemia in patients diagnosed with plantar fasciitis and to descriptively report their clinical features to determine association. Study Design: Cross-sectional Study. Place and Duration of Study: Orthopedics department, Combined Military Hospital, Rawalpindi, Pakistan, from Jan to Dec 2024. Methodology: A total of 200 patients diagnosed with plantar fasciitis were enrolled using non-probability consecutive sampling. Hyperuricemia was defined as >6.0 mg/dL in females and >7.0 mg/dL in males. Clinical features, including pain laterality, BMI, symptom duration, and presence of calcaneal spurs, were recorded. Statistical analysis was conducted using IBM SPSS Statistics for Windows, Version 21.0, and results analyzed. Results: Hyperuricemia was identified in 37(18.5%) out of 200 patients. Among those with hyperuricemia, 19(51.4%) had bilateral pain, 13(35.1%) had right-sided pain, and 5(13.5%) had left-sided pain. The majority were overweight or obese, and symptom duration was more than six months in 23(62.2%) of cases. No significant trends or patterns were observed when examining symptom duration, gender, BMI, or calcaneal spur laterality within these patients. Conclusion: Hyperuricemia was present in 18.5% of patients with plantar fasciitis. Although certain patterns were observed, there was no consistent trend linking hyperuricemia with specific clinical features. Routine uric acid testing may not be necessary in plantar fasciitis patients unless clinical suspicion of inflammatory arthropathy is present.